Utilization of Remote Sensing Images for Compiling The Characteristics Map of Indramayu Beach, West Java - Adjisuci, Arifah Fadhilah; Sewiko, Roni; Mawardi, Sonny; Anasri, Anasri (Politeknik Kelautan dan Perikanan Karawang, 2022)
The beach has an important role in the development and economy of a region. Therefore, it is important to understand the condition and characteristics of the coast so that it can be managed and developed wisely. One way to understand the condition of the beach is through making a map of the characteristics of the beach. A coastal characteristic map is a graphical representation of the conditions and characteristics of the geology, geography, and hydrology of a coast. Making a coastal characteristic map with remote sensing requires several steps, namely: 1). satellite data collection: Pre-processing satellite data; 2). classification of satellite data; 3). satellite data analysis; and finally 4). making a coastal characteristic map. The area that is the fabric material is the beach of Indramayu Regency, West Java. Based on the analysis and interpretation of 2015 Landsat 8 (LDCM) image data, 2020 Sentinel 2 Image data, BATNAS, and DEMNAS data, it is known that the characteristics of the Indramayu beach are that it has geo-quaternary building materials which include: (a) coastal bunds, ( b) swamp deposits, (c) shallow marine deposits, (d) sand deposits, (e) flood plains, (f) river deposits, and (g) floodplain deposits. The morphology includes: (a) beach sand plains, (b) concave coastal swamps, (c) old beach bunds, (d) young beach bunds, (e) alluvial plains, (f) flood plains, and (g) fan plains delta. Finally, it has a distribution of surface sediments on the seabed which includes: (a) sand, (b) silt, gravelly sand, (d) slightly gravelly silt, (e) slightly gravelly sandy mud, and (f) gravelly mud.